Transitivity System and Grammatical Complexity Variations of Interlingual translation: English-Malay Subtitle of Avatar - Robith Khoiril Umam (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2020)
The two main aspects to be considered in translating source language are linguistics and non linguistic. Transitivity system and gramatical complexity belong to the aspect of linguistic and should be maintained by the translator to translate the source language accurately. The objectives of this study are (1) to describe the system of transitivity and grammatical complexity variations in interlingual translation: English-Malay subtitle of Avatar, (2) to describe the factors that motivate the occurance of the variations, (3) to desscribe the effects of the occurance of the variations in aspect of accuracy and acceptability. The result of data analysis shows that the variation of transitivity system and gramatical complexity is very low. The factor motivating the occurrence of variation are intratextual context, intertextual context and situational context. The occuring variations bring negative effect on accuracy and acceptability of the translation.